2020
DOI: 10.1002/ca.23558
|View full text |Cite
|
Sign up to set email alerts
|

Biometry of thenar muscle origins on the flexor retinaculum

Abstract: The transverse carpal ligament (TCL), the main part of the flexor retinaculum, serves as an anchor for the thenar muscles: abductor pollicis brevis (APB), superficial head of the flexor pollicis brevis (sFPB), and opponens pollicis (OPP). Biomechanically, the thenar muscles rely on their TCL anchoring to transmit muscle contractions distally for thumb force and motion production, and reciprocally, muscle contraction interacts with the TCL at the proximal end through the origins. However, scarce knowledge exist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…13,15 Loss and Li dissected 10 cadaveric specimens examining the origin of distributions of the individual thenar muscles. 26 It is possible that hypertrophy due to use, and specific anatomical variants, may predispose certain individuals to CTS without any of the background conditions known to be associated with CTS. In this study, the measure of average muscle depth may account for the high anatomical variability seen in the axial plane, but it fails to capture variability between wrists in the coronal plane of the palm.…”
Section: Discussionmentioning
confidence: 99%
“…13,15 Loss and Li dissected 10 cadaveric specimens examining the origin of distributions of the individual thenar muscles. 26 It is possible that hypertrophy due to use, and specific anatomical variants, may predispose certain individuals to CTS without any of the background conditions known to be associated with CTS. In this study, the measure of average muscle depth may account for the high anatomical variability seen in the axial plane, but it fails to capture variability between wrists in the coronal plane of the palm.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies investigating thenar muscle attachment to the TCL mainly used cadaveric specimens. Loss and Li 9 digitized the footprints of cadaveric muscle origins and reported that 36% of the TCL surface areas was occupied by the thenar muscles. Kung et al 8 quantified that 68% of thenar muscle origin was on the TCL as compared with 24% for hypothenar muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have examined the muscle distribution on the ligament by direct exposure using cadaveric experiments. 8,9 However, there is a lack of in vivo studies on how the ligament is covered by the thenar and hypothenar muscles. Therefore, the purpose of this study was to examine the coverage of thenar and hypothenar muscles on the TCL in the carpal tunnel cross-section at hook of hamate level through in vivo ultrasound imaging.…”
mentioning
confidence: 99%